Polyphenolic composition and bioactive properties of Cynara cardunculus var. altilis petioles: influence of the harvesting time - Mandim, Filipa (2022)
Cardoon (Cynara cardunculus L.) belongs to the Asteraceae family and is native to the Mediterranean basin. It comprises three varieties: the wild cardoon or var. sylvestris, the domesticated cardoon (i.e., var. altilis DC.), and the globe artichoke (i.e., var. Scolymus). 1 This species is highly consumed for culinary and medicinal purposes in the Mediterranean countries, partly due to its attributed properties (e.g., choleretic, diuretic, hypocholesterolemic, hepatoprotective). It also has several industrial applications in different sectors (e.g., cheese manufacturing, pharmacy, production of bioenergy and biomass), which may contribute significantly to the economic valorisation of the species. Several studies refer to the influence that parameters such as the plant tissue, genetic information, and maturation stage may have on the phenolic compounds composition and, therefore, on its biological activities,1,2 so that its most efficient use is gaining attention. For this reason, the present work aims to valorise underused parts of cardoon and, simultaneously, evaluate the effect of harvesting time on the phenolic composition and biological potential of cardoon petioles. Cardoon petioles were collected in central Greece throughout the full growth cycle at sixteen harvest times (samples P1 – plant regrowth to P16 – plant senescence). The polyphenolic composition was analysed by HPLC-DAD-ESI/MS. The antioxidant activity was evaluated using two cell-based assays: thiobarbituric acid reactive substances (TBARS) formation inhibition and oxidative haemolysis inhibition (OxHLIA). The anti-inflammatory activity was determined through the extracts capacity to inhibit the pro-inflammatory mediator nitric oxide (NO) using a murine macrophage cell line (RAW 246.7). The cytotoxic potential was evaluated against four tumour cell lines (breast carcinoma – MCF-7; non-small cell lung cancer – NCI-H460; hepatocellular carcinoma – HepG2; cervical carcinoma – HeLa), and the hepatotoxicity was determined against a non-tumour cell line (PLP2) by the sulforhodamine B assay. Fifteen phenolic compounds (10 phenolic acids and 5 flavone/ol glycosides) were tentatively identified. 5-O-Caffeoylquinic and cis 3,5-O-dicaffeoylquinic acids were the phenolic compounds present in the highest abundance in the studied stages of maturation. Samples at more advanced maturation stages presented the highest content in polyphenols (101 mg/g extract), and the highest capacity to inhibit the formation of TBARS (IC50 = 5.0 μg/mL). On the other hand, samples at intermediate maturation stages exhibited the highest cytotoxic and anti-inflammatory activities. Moreover, samples of immature petioles stood out with the highest effectiveness against oxidative haemolysis (IC50 = 65 and 180 μg/mL at Δt of 60 and 120 min, respectively). In conclusion, our results indicate a significant effect of harvesting time on bioactive properties and chemical composition of cardoon petioles. However, further studies are needed to correlate specific compounds with the biological properties demonstrated by cardoon petioles, as well to define the optimum harvesting time and the application of agronomic practices (e.g., irrigation, fertilization) for obtaining the highest bioactive potential.